Nurse’s Health Education in Families of Pediatric Surgical Clients - Elsa Naviati; Sari Sudarmiati (Universitas Muhammadiyah Semarang, 2018)
Health education is one important component in caring for children with surgical cases. Health education is done to clients and families as an intervention of various nursing problems that appear both pre and post surgery. This study aims to find out how the implementation of health education provided by nurses to families of child surgical clients. This research method is descriptive qualitative phenomenology by using in-depth interview. The number of participants was 5 nurses. The amount is determined after the researchers assume that the research data saturated. The research produced five themes: preoperative health education, postoperative health education, postoperative nutrition, surgical wound care and post operative post pain. The health education provided by the majority nurses is physical. Psychosocial should also be a topic in health education provided by nurses to clients of children and their families.